Unravelling the function of the rice orthologues of the F-box gene HAWAIIAN SKIRT (HWS) in plant development - Borna, Rita Sarah (2018)
The HAWAIIAN SKIRT (HWS) gene from Arabidopsis encodes an F-box protein of 412 amino acids. F-box proteins play a critical role in controlling degradation of cellular proteins. Previous studies revealed that in Arabidopsis, loss of HWS function induced sepal fusion and delayed organ abscission greater growth of both aerial and root portions and bigger seeds. These observations suggest that the target substrate(s) for HWS play(s) a key role in maintenance of organ growth and overall plant development. As rice is one of the major food crops for world population, investigating the role of HWS orthologues in the developmental stages of rice has great importance. HWS has two putative orthologues in rice: - Kelch-domain containing Fbox protein1 (OsFBK1, Os01g47050) and ERECTA PANICLE 3/ LARGER PANICLE (EP3/ LP, Os02g15950). The aim of this research was to characterise and to understand the role of the HWS rice orthologues, OsFBK1 and EP3 by generating and studying rice gain and loss of function, and promoter reporter fusion lines from OsFBK1 and EP3. RT-PCR and qRT-PCR analyses in wild type plants revealed that OsFBK1 and EP3 transcripts were present throughout the development of rice plants. Confocal laser scanning microscopy of promoter-reporter gene fusion lines of OsFBK1 and EP3 revealed that OsFBK1 expression was restricted to root cap cells (nuclear localized), mature pollen grains and stomata; whereas EP3 expression was present in primary and lateral roots, coleoptiles, leaves and floral organs tissues. Morphometric analysis revealed that differential expression of OsFBK1 causes decreased plant height at early stages, decreased root length, decreased tiller number and decreased flag leaf length. In reproductive tissue, OsFBK1 differential expression causes decreased spikelet, anther and stigma area; and increased stigma number. OsFBK1 overexpression decreases plant height at early stages and decreases root length. OsFBK1 overexpression also caused increased spikelet, anther and stigma area; and increased glume and anther number. Yield analyses showed that upregulation OsFBK1 results in low grain filling with bigger seeds. EP3 loss of function increases in plant height and increases flag leaf width, while opposite phenotypes are observed when EP3 is overexpressed. Flower phenotypic analyses revealed that knockout of EP3 caused increased spikelet, anther and stigma area, with increased stigma and spikelet number. Additionally, sometimes tumours form in flower stigmas in loss of function EP3 plants. EP3 overexpression caused reduced spikelet and anther area. Yield analysis showed that both upregulation and down regulation of EP3 caused reduced grain filling and shortened grain length. Loss of function EP3 and up regulation of OsFBK1 together can caused increased glume stigma and carpel number, and severe yield loss. Previously we demonstrated that ep3 mutants are associated with declined photosynthetic assimilation because of smaller size of stomatal guard cells. Here we identified that OsFBK1 also affects photosynthetic assimilation by controlling stomata size and stomatal aperture. qRT analyses to identify downstream genes regulated by OsFBK1 and EP3 demonstrated that EP3 affect OsMIR164 and their targets OsNAM and OsNAC1, while OsFBK1 positively regulates OsNAC1 without involving OsMIR164. EP3 positively regulates the core microRNA biogenesis pathway genes OsDCL1, OsWAF1, OsDDL, OsSE, and OsHASTY, while, OsFBK1 negatively regulates OsDDL; and positively regulates OsWAF1, OsSE and OsHASTY with no effect on OsDCL1. OsFBK1 and EP3 produce pleiotropic effects on plant development like their HWS Arabidopsis orthologue. By using the strategy of downregulating and upregulating OsFBK1 and EP3 we have showed the importance of these genes on plant development and yield in rice. qRT analyses demonstrated that OsFBK1 and EP3 alter expression levels of NAC gene- OsNAM and OsNAC1; and microRNA pathway genes OsDDL, OsSE, OsDCL1, OsWAF1 and OsHASTY. Future analyses are required to identify the under lying mechanism of all these effects.